QUALITY OF INDIHOME SERVICE RESPONSIBILITY IN CUSTOMER COMPLAINTS (JIKE : Jurnal Ilmu Komunikasi Efek, 2024)
The quality of responsibility has a role that cannot be separated from the desire of every company that wants all consumers to feel satisfaction with the products and services that have been sold. Therefore, the implementation of the testing process and also re-checking in order to realize the best product quality so that it has the best quality from other providers and is suitable for use. It takes responsibility from PT. Telkom is improving the quality of internet services to be able to always satisfy customers and provide a positive response as quickly as possible so that customers do not wait too long. This research method uses qualitative research with a descriptive method. In handling company cases and maintaining the company's reputation from PT. TELKOM, the company has various ways to make its customers always loyal to using IndiHome.